Characterization and genomic Analysis of a novel Pseudomonas phage vB_PsaP_M1, representing a new viral family, Psaeviridae - Ren, Linyi; Liu, Yundan; Liang, Yantao; Liu, Baohong; McMinn, Andrew; Zheng, Kaiyang; Wang, Ziyue; Wang, Hongmin; Shao, Hongbing; Sung, Yeong Yik; Mok, Wen Jye; Wong, Li Lian; et al. (Frontiers in Marine Science, 2022)
Pseudomonas is a ubiquitous and ambiguous opportunistic pathogen, and plays an important ecological role in the ocean. Here, a new species, Pseudomonas phage vB_PsaP_M1, is described, which was isolated from the surface coastal waters of Qingdao, China. vB_PsaP_M1 contains a linear, double-stranded 89,387-bp genome with a GC content of 41.04% and encoding 184 putative open reading frames (ORFs). There were 50 conservative domains were predicted with BLASTp, including two auxiliary metabolic genes (Phosphate-inducible gene phoH and signal peptide peptidase A, sppA). Phylogenetic analysis of whole genome amino acid sequence and comparative genomic analysis showed that vB_PsaP_M1 has a distant evolutionary relationship with previously isolated viruses and can be grouped into a family-level novel viral cluster (VC_61) with eleven uncultured, assembled viral genomes, named as Psaeviridae. Psaeviridae contains two ORFs (ORFs 117 and 127), which were not detected in the genomes of other viral families, confirming the proposal for a new family. Combined with its ability to infect Pseudomonas and its representation of an unstudied viral family, vB_PsaP_M1 may be an important and novel model system for the study of interactions between viruses and host cells in marine ecosystems.